Thermoelectric properties of topological insulator Bi2Te3, Sb2Te3, and Bi2Se3 thin film quantum wells - Osterhage, Hermann; Gooth, Johannes; Hamdou, Bacel; Gwozdz, Paul; Zierold, Robert; Nielsch, Kornelius (Applied Physics Letters, 2014)
The thermoelectric (TE) figure of merit ZT of topological insulator Bi2Te3, Sb2Te3, and Bi2Se3 thin film quantum wells is calculated for thicknesses below 10 nm, for which hybridization of the surface states as well as quantum confinement in the bulk are individually predicted to enhance ZT. Here, the question is addressed what ZT can be expected from coexisting surface and bulk states in such quantum wells. It is demonstrated that the parallel contributing bulk and surface channels tend to cancel each other out. This is because the surface-to-volume ratios of the thin films prevent the domination of transport through a single channel and because the individual bulk and surface ZTs are optimized at different Fermi levels.
CRIS-Team Scopus Importer:2023-03-20